The Effect Requirements Selling in the Marketplace for Security Against Buyer Trust - Aisyah, Euis Sitinur; Harahap, Eka Purnama; Salsabila, Nabilah (APTISI Transactions on Management (ATM), 2020)
Marketplace is a website or online application that facilitates the buying and selling of various stores. Marketplace is of interest to sellers as well as buyers of places to transact. But fraud is one of the annoying things in a Marketplace. It is evident that for a security Marketplace as well as trust for shoppers is a top priority Marketplace. So how the requirements on Marketplace for sellers can sell on Marketplace. Does it affect fraud prevention to make the Marketplace a Marketplace of interest in Indonesia. Using the results of Marketplace statistical research studies from the biggest Marketplace position in Indonesia. View the requirements applied by the largest marketplace to see how the requirements are affected. Results show that the requirements for becoming a seller on Marketplace have a significant impact on the security and buyer confidence. It is seen that with the authenticity of the seller data, the buyer will better trust the marketplace to reduce fraud. Because if the seller cheats the buyer it will affect the good image and trust of the buyer. That way the marketplace will suffer losses. It is hoped that only the Marketplace is huge but the growing small Marketplace has increased the requirements for sellers to avoid fake identities for sellers who want to cheat.